2009
DOI: 10.1016/j.jmmm.2008.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Micro-patterning of NdFeB and SmCo magnet films for integration into micro-electro-mechanical-systems

Abstract: The integration of high performance RE-TM (NdFeB and SmCo) hard magnetic films into Micro-Electro-Mechanical-Systems (MEMS) requires their patterning at the micron scale.In this paper we report on the applicability of standard micro-fabrication steps (film deposition onto topographically patterned substrates, wet etching and planarization) to the patterning of 5 µm thick RE-TM films. While NdFeB comprehensively fills micron scaled trenches in patterned substrates, SmCo deposits are characterized by poor fillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(48 citation statements)
references
References 14 publications
0
46
0
2
Order By: Relevance
“…This technique leads to irreversible bonding between the PDMS layer and the PDMS channel, but, if required, the resulting closed chamber formed on top of the micromagnet array can be pulled off the substrate, leaving the TMP film reusable for further experiments. 19 The thin PDMS membrane also contributes to reduce non-specific adsorption of cells observable on uncoated magnetic films.…”
Section: A Single Droplet Trapping Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique leads to irreversible bonding between the PDMS layer and the PDMS channel, but, if required, the resulting closed chamber formed on top of the micromagnet array can be pulled off the substrate, leaving the TMP film reusable for further experiments. 19 The thin PDMS membrane also contributes to reduce non-specific adsorption of cells observable on uncoated magnetic films.…”
Section: A Single Droplet Trapping Experimentsmentioning
confidence: 99%
“…Micro-patterning of such films, using topographic (lithography) 19 or thermo-magnetic (temperature control of magnetization reversal) 20 approaches, produces micron-sized permanent magnets characterized by stray magnetic field gradients as high as 10 6 T/m. 21 The flat surface of thermo-magnetically patterned films facilitates their integration into microfluidic devices, and they have been used to trap magnetic particles (SiO 2 and polystyrene particles containing magnetic nanoparticles) within such a device.…”
mentioning
confidence: 99%
“…Thin-film NdFeB/α-Fe nanocomposite magnets consisting of dispersed hard and soft magnetic phases with the grain size in the 10-30 nm range have been reported (Shindo et al, 1997;Yang and Kim, 1999) with high reduced remanent magnetization and magnetic energy product. These materials have wide application as permanent magnets and are useful in micro-mechanical devices (Walther et al, 2009) and may have numerous applications in magneto-electronic devices. Generally, all the as-deposited and below 550°C annealed Nd-Fe-B thin films have H c values of up to 200 Oe.…”
Section: Relationship Between the Magnetism Of Nd 2 Fe 14 B/(α-fe Fementioning
confidence: 99%
“…Based on the data presented in Figure 14, α and β coefficients in the temperature range 25°C÷150°C for Ta/[NdFeBNbCu(180 nm)/Co(2 nm)]x3/Ta thin film are about −0.025%/°C and −0.39%/°C, respectively. It can be observed that low values of the α and β coefficients for Ta/[NdFeBNbCu(180 nm)/Co(2 nm)]x3/Ta thin film in the temperature range 25°C÷150°C satisfy the needs of planar permanent magnets as actuator elements for MEMS applications (Walther et al, 2009 …”
Section: Thermal Stabilitymentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Although (BH) max of an isotropic Nd-Fe-B film is inferior to that of an anisotropic one, 8,9 the flexibility of magnetization is attractive in the practical applications such as miniaturized motors. For example, Töpfer et al reported a multipolarly magnetized isotropic Nd-Fe-B film prepared by a screen printing method.…”
Section: Introductionmentioning
confidence: 99%